Epistemic immediacy and distance as the basis of the Croatian TAM system - Stanojević, Mateusz-Milan (2012)
This paper explores the Croatian tense-aspect-mood system on the basis of epistemic immediacy and distance. The aim of the paper is to show that epistemic stance is the overarching notion behind the following phenomena: 1) l-participle vs. n-participle use in Croatian 2) the distinction in the use of the Present Tense vs. l-participle constructions 3) the distinction in the use of the Aorist vs. l-participle constructions. In order to do this, we have performed a number of corpus studies in the Croatian National Corpus: a study of a random sample of 1000 tokens each of l- and n-participles, a study of Aorist forms of 6 verbs (dobiti ‘get’, doći ‘come’, kupiti ‘buy’, otići ‘leave’, reći ‘say’, vidjeti ‘see’) and a study of a random sample of 500 sentences each of conditional clauses with da 'if', ako 'if', kad(a) 'when'. The samples were manually coded for: the tense used, time reference, person, number, appearance of auxiliary (and a number of other categories). Overall, the results show that the Perfect Tense is by far the most frequent l-participle construction (over 80% of the cases), and that the combination of the Present Tense of the be auxiliary with the n-participle is the most frequent n-participle construction (over 90%). The Present Conditional is the second most frequent l-participle form (some 12%). Whereas the Perfect Tense tends to be used with a precise time reference, the Aorist tends to be used without precise time identification. The study of the conditionals showed certain limitations in the combinations of tenses in the protasis and apodosis: with ako ‘if’ the protasis–apodosis combination tends to be Present-Present, with kad(a) ‘when’ the protasis–apodosis it tends to be Present-Present and Perfect-Perfect, and with counterfactual conditionals with da ‘if’ it tends to be Perfect-Present Conditional. Generally, all of these results are compatible with an aspectual account of the Croatian TAM system. The l-participle refers to a non-permanent property of the first participant in the action chain (cf. Langacker 1987), and is a viewpoint operator (in the sense of DeLancey 1981) which expresses retrospective aspect generalized to epistemic distance (Stanojević 2011). The n-participle is complementary to it: it reverses the energy flow in the action chain (Belaj 2004:35) focusing on the target domain, and refers to a permanent property of the target domain participant. The Aorist and the Present Tense express various degrees of epistemic immediacy (Stanojević and Geld 2011 ; Geld and Zovko Dinković 2007), for various reasons: because of perfectivity (Aorist) and imperfectivity (the Present Tense). Ako ‘if’ and kad(a) ‘when’ work within the epistemic plane set up by the verbal forms (in the sense of Dancygier and Trnavac 2007), whereas da ‘that’ is a space builder which defaults the use of the Present Tense to epistemic immediacy, and the Perfect Tense to epistemic distance. Ultimately, this account suggests that the Croatian TAM system is largely aspect-based, which is in harmony with cross-Slavic and diachronic evidence regarding l-participles, n-participles and conditionals. References Belaj, Branimir. 2004. Pasivna rečenica. Osijek: Filozofski fakultet Sveučilišta Josipa Jurja Strossmayera. Dancygier, Barbara, and Radoslava Trnavac. 2007. Conjunctions, verb forms, and epistemic stance in Polish and Serbian predictive conditionals. In Cognitive Paths into the Slavic Domain, ed. Dagmar Divjak and Agata Kochańska, 181-218. Cognitive Linguistics Research. Berlin, New York: Mouton de Gruyter. DeLancey, Scott. 1981. An Interpretation of Split Ergativity and Related Patterns. Language 57, no. 3: 626-657. Geld, Renata, and Irena Zovko Dinković. 2007. Perfectives, imperfectives and the Croatian present tense. In Cognitive Paths into the Slavic Domain, ed. Dagmar Divjak and Agata Kochańska, 111-148. Cognitive Linguistics Research. Berlin, New York: Mouton de Gruyter. Langacker, Ronald W. 1987. Foundations of Cognitive Grammar. Vol. 1. Stanford: Stanford University Press. Stanojević, Mateusz-Milan. 2011. Modeling epistemic distance: the Croatian l-participle. Suvremena lingvistika 37 no. 72: 219-239. Stanojević, Mateusz-Milan, and Renata Geld. 2011. New current relevance in Croatian: epistemic immediacy and the aorist. In Cognitive Approaches to Tense, Aspect, and Epistemic Modality, ed. Frank Brisard and Adeline Patard, 159-179. Amsterdam, Philadelphia: John Benjamins.